Analisis Faktor yang Mempengaruhi Produksi Air Susu Ibu (ASI) pada Ibu Menyusui yang Bekerja - Anita Rahmawati; Bisepta Prayogi (Journal of Ners and Midwifery, 2017)
Working mom's busyness affects the physical and psychological condition of the mother inhibiting the smoothness of milk production. The application of hypnobreastfeeding makes the mother relaxation so as to increase the hormone prolactin and oxytocin for smooth milk production. The procedure of hypnobreastfeeding by giving a positive suggestion/affirmation sentence in the mother's unconscious mind can increase the mother's confidence in the breastfeeding process. The purpose of this study was to explain the effect of hypnobreastfeeding on breast milk production on breastfeeding working mothers. This study used one group pretest posttest design. 25 breastfeeding working mothers were taken by consecutive samping. Hypnobreastfeeding is done independently after being given 1x workshop and performed every day at least 2x a day before breastfeeding. Breastmilk production is measured for 7 days before and after hypnobreastfeeding using a measuring cup based on the volume of dairy milk in a day. The average milk production before treatment 210 ml / day and after treatment to 255 ml / day. Data analysis using paired t-test with significant value Î± = 0,05 got p value = 0.000 indicating hypnobreastfeeding effect to milk production in working breastfeeding mother. Nurses or other health workers may recommend hypnobreastfeeding as one of the lactation management methods to increase breastfeeding production, especially in working breastfeeding mothers.